Westonci.ca is your trusted source for finding answers to a wide range of questions, backed by a knowledgeable community. Join our platform to connect with experts ready to provide detailed answers to your questions in various areas. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
To determine the values of [tex]\( x \)[/tex] for which the second derivative [tex]\( f''(x) \)[/tex] of the function [tex]\( f(x) = \frac{5}{2} x^2 e^x \)[/tex] is zero, let us follow these steps:
1. Compute the first derivative [tex]\( f'(x) \)[/tex]:
- We need to apply the product rule for the differentiation of [tex]\( f(x) \)[/tex]. The product rule states that [tex]\( (uv)' = u'v + uv' \)[/tex], where [tex]\( u = \frac{5}{2} x^2 \)[/tex] and [tex]\( v = e^x \)[/tex].
- The derivative of [tex]\( u = \frac{5}{2} x^2 \)[/tex] is [tex]\( u' = 5x \)[/tex].
- The derivative of [tex]\( v = e^x \)[/tex] is [tex]\( v' = e^x \)[/tex].
- Using the product rule:
[tex]\[ f'(x) = \left( \frac{5}{2} x^2 \right)' e^x + \frac{5}{2} x^2 (e^x)' = 5x e^x + \frac{5}{2} x^2 e^x = e^x \left( 5x + \frac{5}{2} x^2 \right) \][/tex]
[tex]\[ f'(x) = \frac{5}{2} x e^x (2 + x) \][/tex]
2. Compute the second derivative [tex]\( f''(x) \)[/tex]:
- Again, apply the product rule to [tex]\( f'(x) = \frac{5}{2} e^x x (2 + x) \)[/tex]. We treat this as a product of two functions:
- Let [tex]\( u = \frac{5}{2} x (2 + x) \)[/tex] and [tex]\( v = e^x \)[/tex].
- The derivative of [tex]\( u \)[/tex] is:
[tex]\[ u' = \frac{5}{2} (2 + x + x) = \frac{5}{2} (2 + 2x) = \frac{5}{2} \cdot 2 (1 + x) = 5 (1 + x) \][/tex]
- The derivative of [tex]\( v = e^x \)[/tex] is [tex]\( v' = e^x \)[/tex].
- Applying the product rule again:
[tex]\[ f''(x) = \left( \frac{5}{2} x (2 + x) \right)' e^x + \frac{5}{2} x (2 + x) \left( e^x \right)' \][/tex]
[tex]\[ f''(x) = 5 (1 + x) e^x + \frac{5}{2} x (2 + x) e^x = e^x \left( 5 (1 + x) + \frac{5}{2} x (2 + x) \right) \][/tex]
[tex]\[ f''(x) = e^x \left( 5 + 5x + \frac{5}{2}(2x + x^2) \right) = e^x \left( 5 + 5x + 5x + \frac{5}{2} x^2 \right) \][/tex]
[tex]\[ f''(x) = e^x \left( 5 + 10x + \frac{5}{2} x^2 \right) = e^x \left( \frac{10 + 20x + 5x^2}{2} \right) = \frac{5}{2} e^x (2 + 4x + x^2) \][/tex]
3. Determine when [tex]\( f''(x) = 0 \)[/tex]:
- Since [tex]\( e^x \)[/tex] is never zero, we only need to solve:
[tex]\[ 2 + 4x + x^2 = 0 \][/tex]
- This is a quadratic equation. Solving it using the quadratic formula [tex]\( x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \)[/tex], where [tex]\( a = 1 \)[/tex], [tex]\( b = 4 \)[/tex], and [tex]\( c = 2 \)[/tex]:
[tex]\[ x = \frac{-4 \pm \sqrt{4^2 - 4 \cdot 1 \cdot 2}}{2 \cdot 1} = \frac{-4 \pm \sqrt{16 - 8}}{2} = \frac{-4 \pm \sqrt{8}}{2} = \frac{-4 \pm 2\sqrt{2}}{2} = -2 \pm \sqrt{2} \][/tex]
- Therefore, the solutions are:
[tex]\[ x = -2 + \sqrt{2} \quad \text{and} \quad x = -2 - \sqrt{2} \][/tex]
Therefore, the solutions can be approximated to:
[tex]\[ x \approx -3.414 \quad \text{and} \quad x \approx -0.586 \][/tex]
Given these calculations, the value of [tex]\( x \)[/tex] for which the second derivative [tex]\( f''(x) \)[/tex] equals zero is approximately [tex]\( x \approx -3.414 \)[/tex] and [tex]\( x \approx -0.586 \)[/tex], which do not match any of the given multiple-choice options exactly. This might indicate either the choices were not meant to match exactly numerical solutions or an approximation discrepancy. Hence, the choices 0, [tex]\(\ln 5\)[/tex], [tex]\(e^5\)[/tex], and [tex]\(5e\)[/tex] are not correct as none of them approximate the obtained solutions.
1. Compute the first derivative [tex]\( f'(x) \)[/tex]:
- We need to apply the product rule for the differentiation of [tex]\( f(x) \)[/tex]. The product rule states that [tex]\( (uv)' = u'v + uv' \)[/tex], where [tex]\( u = \frac{5}{2} x^2 \)[/tex] and [tex]\( v = e^x \)[/tex].
- The derivative of [tex]\( u = \frac{5}{2} x^2 \)[/tex] is [tex]\( u' = 5x \)[/tex].
- The derivative of [tex]\( v = e^x \)[/tex] is [tex]\( v' = e^x \)[/tex].
- Using the product rule:
[tex]\[ f'(x) = \left( \frac{5}{2} x^2 \right)' e^x + \frac{5}{2} x^2 (e^x)' = 5x e^x + \frac{5}{2} x^2 e^x = e^x \left( 5x + \frac{5}{2} x^2 \right) \][/tex]
[tex]\[ f'(x) = \frac{5}{2} x e^x (2 + x) \][/tex]
2. Compute the second derivative [tex]\( f''(x) \)[/tex]:
- Again, apply the product rule to [tex]\( f'(x) = \frac{5}{2} e^x x (2 + x) \)[/tex]. We treat this as a product of two functions:
- Let [tex]\( u = \frac{5}{2} x (2 + x) \)[/tex] and [tex]\( v = e^x \)[/tex].
- The derivative of [tex]\( u \)[/tex] is:
[tex]\[ u' = \frac{5}{2} (2 + x + x) = \frac{5}{2} (2 + 2x) = \frac{5}{2} \cdot 2 (1 + x) = 5 (1 + x) \][/tex]
- The derivative of [tex]\( v = e^x \)[/tex] is [tex]\( v' = e^x \)[/tex].
- Applying the product rule again:
[tex]\[ f''(x) = \left( \frac{5}{2} x (2 + x) \right)' e^x + \frac{5}{2} x (2 + x) \left( e^x \right)' \][/tex]
[tex]\[ f''(x) = 5 (1 + x) e^x + \frac{5}{2} x (2 + x) e^x = e^x \left( 5 (1 + x) + \frac{5}{2} x (2 + x) \right) \][/tex]
[tex]\[ f''(x) = e^x \left( 5 + 5x + \frac{5}{2}(2x + x^2) \right) = e^x \left( 5 + 5x + 5x + \frac{5}{2} x^2 \right) \][/tex]
[tex]\[ f''(x) = e^x \left( 5 + 10x + \frac{5}{2} x^2 \right) = e^x \left( \frac{10 + 20x + 5x^2}{2} \right) = \frac{5}{2} e^x (2 + 4x + x^2) \][/tex]
3. Determine when [tex]\( f''(x) = 0 \)[/tex]:
- Since [tex]\( e^x \)[/tex] is never zero, we only need to solve:
[tex]\[ 2 + 4x + x^2 = 0 \][/tex]
- This is a quadratic equation. Solving it using the quadratic formula [tex]\( x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \)[/tex], where [tex]\( a = 1 \)[/tex], [tex]\( b = 4 \)[/tex], and [tex]\( c = 2 \)[/tex]:
[tex]\[ x = \frac{-4 \pm \sqrt{4^2 - 4 \cdot 1 \cdot 2}}{2 \cdot 1} = \frac{-4 \pm \sqrt{16 - 8}}{2} = \frac{-4 \pm \sqrt{8}}{2} = \frac{-4 \pm 2\sqrt{2}}{2} = -2 \pm \sqrt{2} \][/tex]
- Therefore, the solutions are:
[tex]\[ x = -2 + \sqrt{2} \quad \text{and} \quad x = -2 - \sqrt{2} \][/tex]
Therefore, the solutions can be approximated to:
[tex]\[ x \approx -3.414 \quad \text{and} \quad x \approx -0.586 \][/tex]
Given these calculations, the value of [tex]\( x \)[/tex] for which the second derivative [tex]\( f''(x) \)[/tex] equals zero is approximately [tex]\( x \approx -3.414 \)[/tex] and [tex]\( x \approx -0.586 \)[/tex], which do not match any of the given multiple-choice options exactly. This might indicate either the choices were not meant to match exactly numerical solutions or an approximation discrepancy. Hence, the choices 0, [tex]\(\ln 5\)[/tex], [tex]\(e^5\)[/tex], and [tex]\(5e\)[/tex] are not correct as none of them approximate the obtained solutions.
We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.